TRANSFORMATION TO PRODUCT DESIGN FEATURES MODERN CULTURE - Agus Setiawan (Jurnal Ilmiah Dinamika Teknik, 2011)
With beautiful art and primitive ancestors to provide a visual form of crafts, native cultures offer great potential to improve the design and become a recognized global market value. Evidence suggests a very high prospect for some local culture into cultural elements that are important in the design of future applications. The purpose of this paper is to explore the meaning of cultural objects and to extract the local culture of their cultural traits. This paper tries to describe how to improve the features of the local culture by using new production technology, which can be converted into a modern product that meets the needs of the contemporary consumer market. Certain cultural objects chosen to describe the performance analysis of cultural features, how it is used, cultural meaning, operational interface, and the scenario in which it is used. Finally, this paper established a cultural product design model that is intended to provide designers with a valuable reference for designing a product cross-cultural success. Keywords: Feature Culture, Cultural Transfer, Cultural Product Design, Industrial Design